The Relationship Between Self-Esteem Level, Self-Esteem Stability, and Cardiovascular Reactions to Performance Feedback. [article]. - Seery, Mark D.
The Authors examined the notion that individuals with unstable high self- esteem posses implicit self-doubt. They adopted the framework of the biopsychosocial model of challenge and threat and assessed spontaneous cardiovascular reactions in the face of success versus failure performance feedback. Study 1 revealed predicted interactions between feedback condition, self-esteem level, and self-esteem stability, such that participants with unstable high self-esteem exhibited relative threat (a negative reaction) in the failure condition, whereas those with stable high self-esteem exhibited relative challenge (a positive reaction). Study 2 replicated these results and provided additional evidence against plausible alternative explainations. -- (from the author)
Keywords: Psychology-Periodicals.